Fabrication of gold nanoparticles tethered in heat-cooled calf thymus-deoxyribonucleic acid Langmuir-Blodgett film as effective surface-enhanced Raman scattering sensing platform - Sinha, Rajdeep; Das, Sumit Kumar; Ghosh, Manash; Chowdhury, Joydeep (Frontiers in Chemistry, 2022)
SERS active substrate fabricated through self-assembly of Gold nanoparticles on the disjointed networks of Heat-cooled Calf Thymus DNA (HC-Ct DNA) Langmuir-Blodgett (LB) film has been reported. Adsorption kinetics of HC-Ct DNA molecules at the air-water interface has been studied explicitly. The UV-Vis electronic absorption spectra in conjunction with the FESEM images collectively suggest the presence of H- type aggregated domains most likely owing to plane-to-plane self-association of the HC-Ct DNA molecules aligned vertically on the surface of the LB film. Elemental composition and the morphological features of the as-prepared substrate (APS) are explored from XPS analysis and the FESEM, AFM images respectively. The SERS efficacy of the APS has been tested with trace concentrations of 4-Mercaptopyridine molecule. Finally, this SERS active substrate has also been used for the detection of malathion at ultrasensitive concentrations.